Every picture tells a story: a directive content analysis of the investment model on Instagram posts for new romantic relationships - Goodcase, Eric Thomas (Kansas State University, 2019)
Instagram has become a popular social media site for individuals to post pictures and communicate about their lives to others, including their romantic relationships. These posts may be used to communicate the development of their relationship to their partner, close friends, and family, and thus, may also influence their relationship. Guided by the investment model (Rusbult, 1980), Instagram posts from 18 individuals in a new romantic relationship were coded using directive content analysis over the course of six months to determine how Instagram posts may reflect peoples’ relationship investment, satisfaction, and view of alternatives to their current relationship. Results indicate that relationship investment and satisfaction are represented in a number of ways on Instagram while posts showing views of alternatives were rare. Other posts made included pictures of self, pictures of friends/family, documentation of life events, outside internet content, and animal pictures. This indicates that Instagram behavior may provide insight into relationship investment and relational outcomes, however, there were few relationship costs or view of alternatives present in Instagram posts indicating that Instagram presentation may be overly idealistic and not fully represent the investment model. Future Instagram research could benefit from archiving posts in real time, analyzing other Instagram behaviors, and asking questions about perceptions and motivations of Instagram behavior.
Keywords: Instagram; Romantic Relationship; Investment Model; Social Media; Commitment